89.5k views
5 votes
Answer this step by step 5x^2+3-y^2+3x-6x^2-5y-6+y^2+4

User Fatdragon
by
5.6k points

1 Answer

3 votes

Answer:

Add the new equation to the equation we didn't use in step 1 in order to eliminate one of the variables. Step 3: Solve ... Systems of equations with elimination: 2x-y=14 & -6x+3y=-42 ... Systems of equations with elimination: 6x-6y=-24 & -5x-5y=-60 ... of 2) · Systems of equations number of solutions: y=3x+1 & 2y+4=

Explanation:

hope dis helps!

User Amitection
by
5.8k points